Useful biometric variables in Iberian exuviae of Boyeria irene (Fonscolombe, 1838) (Odonata: Aeshnidae) - Nunes, L.F. (2022)
In species of similar shape and size, biometric analyses make it possible to establish differences. Within one species, biometrics can help researchers to detect differences between populations and analyze their adaptations to environmental conditions. Until now little was known about the biometrics of the Iberian populations of Boyeria irene (Odonata: Aeshnidae), a large species living mainly in southern Europe. Eight biometric variables were studied in male and female exuviae of B. irene collected in three rivers of the Iberian Peninsula, with the objective of ascertaining which are the most suitable populations of this species to study. An analysis of principal components (PCA) shows that lengths of the epiproct, paraproct and prementum are the most influential in each of the three populations. The other variables (head width, body length, length of the gonapophyses, maximum and minimum width of the prementum) proved not to be relevant in this context.